Efficacy and safety of lamivudine treatment in late pregnancy with high HBV DNA: a perspective for mother and infants - Sükran Köse; Melda Türken; İlker Devrim; Cüneyt Taner (Journal of Infection in Developing Countries)
Introduction: Perinatal transmission - from mother to fetus - is one of the main transmission routes of chronic hepatitis B (CHB) infection. Lamivudine therapy has been reported to prevent the replication of hepatitis B virus (HBV) in pregnant women with a high viral load that can lead to perinatal transmission.